MS 1184: Awareness Among Designers and Allied Assistants of the Built Environment in Malaysia - Halimi, Nur Halinda; Yusof, Yussuriani Ome (MAJ - Malaysia Architectural Journal, 2025)
Buildings, products and physical environments that are accessible to individuals of all ages, abilities and circumstances are defined as universal design. In Malaysia, the Malaysian Standard document MS 1184 : 2014 – Universal design and accessibility in the built environment – Code of practice has been made the primary guideline for the designing and planning of the built environment to ensure inclusivity and barrier free for all. High awareness of universal design contributes to effective accessible built environment. However, awareness on universal design and the existence of MS 1184 : 2014 among designers and allied assistants in the field of built environment are still lacking. The objective of this study is to determine the general level of awareness on universal design and MS 1184 : 2014 document among designers and allied assistants in the field of built environment in the Klang Valley. The methodology adopted for this study is quantitative methodology via questionnaire survey. This study managed to attain 349 respondents from built environments designers and allied assistants around the Klang Valley. Results of the study indicates 187 respondents (55%) are aware on MS 1184 : 2014, while the rest are not in the know of the guideline. Findings of this study denote that there are still many designers and allied assistants in the field of built environment who are not aware on universal design and the MS 1184 : 2014 document. From the findings, the study suggests that more initiatives and proactive actions to increase the awareness among designers and allied assistants in the field of built environment in Malaysia. Further studies are recommended to identify what are the factors that contribute to this phenomenon.